3 - Women’s Land Rights and Working Conditions in Large-scale Plantations in Sub-Saharan Africa - Fonjong, Lotsmart (Africa Development, 2021)
Women’s land rights are fundamental for women’s economic empowerment. Increasingly, the nationalization of customary land and the current growth in private land ownership and commercial farming are exerting strong pressure on land and are a threat to women’s usufruct land rights. The discourse over land reforms in most poor African countries like Cameroon is embedded in the evolutionary models where customary landholding systems are changing into state land ownership with greater market integration. These changes are taking place within limited state protection of communal and women’s land rights in the process of land registration. This article discusses the evolution, actors and activities involved in large-scale land acquisitions in the sub region within the framework and women’s rights to land and working conditions in the plantations. Through simple mapping from an in-depth desktop review and some level of field observations and conversations with some of the actors involved in affected localities in Cameroon, the article highlights women’s experiences as customary communal land is transferred into private ownership. In fact, wherever land has been taken up for plantation agriculture, women’s access to land has reduced, making them more vulnerable to hunger, poverty and poor working conditions. This is because women’s land rights have not evolved with the customary evolution into private tenures. Current processes of large-scale land acquisitions should therefore create conditions for women’s participation through a fair degree of equal opportunities, transparency, and accountability to communities, and relevant institutions.